In vitro and in vivo characterization of a novel, highly potent p53-MDM2 inhibitor. Issue 20 (1st November 2018) - Vaupel, Andrea; Holzer, Philipp; Ferretti, Stephane; Guagnano, Vito; Kallen, Joerg; Mah, Robert; Masuya, Keiichi; Ruetz, Stephan; Rynn, Caroline; Schlapbach, Achim; Stachyra, Thérèse; Stutz, Stefan; et al.
Graphical abstract: Highlights: Novel rationally designed p53-MDM2 inhibitor scaffold. Structural proof of concept by x-ray crystallography. Optimization of metabolic stability. In vivo proof of concept with high efficacy. Abstract: Small molecule inhibitors of the p53-MDM2 protein complex are under intense investigation in clinical trials as anti-cancer agents, including our first generation inhibitor NVP-CGM097. We recently described the rational design of a novel pyrazolopyrrolidinone core as a new lead structure and now we report on the synthesis and optimization of this to provide a highly potent lead compound. This new compound displayed excellent oral efficacy in our preclinical mechanistic in vivo model and marked a significant milestone towards the identification of our second generation clinical candidate NVP-HDM201.